Over‐the‐needle trans‐septal access using the cryoballoon delivery sheath and dilator in atrial fibrillation ablation. Issue 7 (13th May 2019) - Ströker, Erwin; De Greef, Yves; Schwagten, Bruno; Kupics, Kaspars; Coutiño, Hugo Enrique; Takarada, Ken; Abugattas, Juan Pablo; Salghetti, Francesca; De Cocker, Jeroen; Stockman, Dirk; Sieira, Juan; Brugada, Pedro; et al.
Abstract: Background: In the setting of second‐generation cryoballoon (CB2) ablation, left atrial (LA) access is generally achieved using a standard sheath (SS) that is exchanged for the 15Fr cryoballoon delivery sheath (CBS) and dilator over a long wire (CBS over‐the‐wire technique, CBS‐W). Our objective was to evaluate the direct use of the CBS to gain LA access, by advancing the latter over the trans‐septal needle (CBS over‐the‐needle technique, CBS‐N), under transesophageal echocardiographic (TEE) guidance. Methods: Consecutive patients who underwent CB2 ablation with the CBS‐N technique were evaluated for feasibility of gaining LA access using TEE guidance and fluoroscopy views. Complications related to the LA access were compared with a matched CBS‐W control group. Subanalysis (30 CBS‐W vs 30 CBS‐N patients) evaluated time‐to‐LA of the CBS: time from superior vena cava (with SS vs CBS) to LA insertion of the CBS, after exchange or directly, respectively. Results: LA access could be achieved in all 505 patients of the CBS‐N group, without technique modification or additional equipment. Challenging interatrial septa were noted in 13% of these patients: previous atrial septal defect repair (1%), hypermobile (10%), aneurysmal (1%), and abnormally thickened/fibrotic (1%). Incidence of complications was similar to the CBS‐W group. Subanalysis showed a shorter time‐to‐LA in the CBS‐N versus CBS‐W group, 72 ± 46 seconds versus 293 ± 180 seconds, P < .001. Conclusions: Our study showed that the CBS‐N technique is feasible and safe under echocardiographic guidance. Without sheath exchange, it simplifies the CB2 procedure, is less costly, time sparing, and might reduce the risk of air embolism.